Morphemes and literacy: A starting point - Bryant, P; Nunes, T (Routledge Taylor and Francis Group, 2006)
We all know that words have meanings, but not everyone understands that the meaning of any word depends on its underlying structure. Words consist of morphemes, which are units of meaning. These morphemes, in our view, are of immense importance in children's learning of the meaning of new words and also in their learning how to read and write familiar and novel words. The aim of our book is to show how important morphemes can be in children's education and how easy it is to enhance their knowledge about morphemes and thus to increase the richness of their vocabulary and the fluency of their reading and writing.